Bifidobacterium breve BB05 alleviates depressive symptoms in mice via the AKT/mTOR pathway - Pan, Yanni; Huang, Qingling; Liang, Yuan; Xie, Yuwuqi; Tan, Fang; Long, Xingyao (Frontiers in Nutrition, 2025)
IntroductionThis study investigates the potential of Bifidobacterium breve BB05 (BB05) in mitigating depressive symptoms in a mouse model of Chronic Unpredictable Mild Stress (CUMS), with fluoxetine as a positive control.Methods and ResultsHigh-dose BB05 (1.0 × 109 CFU/kg, BB05H) significantly reduced anxiety- and depression-like behaviors in CUMS mice, as measured by the open field test, tail suspension test, and forced swim test. BB05 treatment also reduced pathological ileal damage, alleviated inflammation, and lowered serum levels of pro-inflammatory cytokines IL-6 and TNF-α. Additionally, BB05 increased serum 5-HT levels and decreased ACTH concentrations. Mechanistic analysis revealed that BB05 exerts antidepressant effects by activating the AKT/mTOR signaling pathway in the prefrontal cortex, promoting neuroprotection, neurogenesis, and synaptic plasticity.DiscussionThese findings suggest that BB05, particularly at higher doses, effectively alleviates CUMS-induced depressive behaviors and improves physiological outcomes, supporting the use of probiotics as a potential treatment for depression by targeting the AKT/mTOR pathway.